The hour that changes the world : a practical plan for personal prayer - Eastman, Dick (Grand Rapids, Michigan : Baker Book House, 1978)
Includes bibliography
Includes bibliographical references (p. 163-174)
Keywords: Prayer; Prayer -- Christianity; Twelve-step programs -- Religious aspects -- Christianity